Nickel toxicity alters growth patterns and induces oxidative stress response in sweetpotato - Kumar, Sunjeet; Wang, Mengzhao; Liu, Yi; Fahad, Shah; Qayyum, Abdul; Jadoon, Sultan Akbar; Chen, Yanli; Zhu, Guopeng (Frontiers in Plant Science, 2022)
Nickel (Ni) contaminated soil is a persistent risk to plant growth and production worldwide. Therefore, to explore the Ni toxicity levels in sweetpotato production areas, we investigated the influence of different Ni treatments (0, 7.5, 15, 30, and 60 mg L-1) for 15 days on phenotype, Ni uptake, relative water content, gas exchange, photosynthetic pigments, oxidative stress, osmolytes, antioxidants, and enzymes of sweetpotato plants. The results presented that Ni at higher levels (30 and 60 mg L-1) substantially reduced growth, biomass, and root morphological traits. The Pearson correlation analysis suggested that Ni toxicity causes oxidative injuries as persistent augmentation of hydrogen peroxide (H2O2) and malonaldehyde (MDA) and reduced RWC, gas exchange, and photosynthetic pigment. Furthermore, this study revealed that sweetpotato could tolerate moderate Ni treatment (up to 15 mg L-1) by reducing oxidative stress. The results also indicated that the increase in the activities of mentioned osmolytes, antioxidants, and enzymes is not sufficient to overcome the higher Ni toxicity. Based on these results, we suggest using low Ni-contaminated soil for better growth of sweetpotato and also could be used as a phytoremediator in moderate Ni-contaminated soil.